Kecemasan Calon Pengantin dalam Menghadapi Pernikahan - Eprila Eprila; Ira Kusumawaty; Yunike Yunike (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore the perceptions of the bride and groom based on their experiences in obtaining pre-wedding education. This qualitative research used a phenomenological approach by conducting in-depth interviews with nine pairs of prospective brides. A qualitative research method with a phenomenological study approach is applied in this study. The collection process is carried out through in-depth interviews, recording, and documentation of activities. For triangulation needs, discussions have been conducted with religious affairs office staff who provide briefings for the prospective bride and groom. The results of the direct interview recordings were written in transcript form and analyzed using content analysis. The results showed five themes, including worries before marriage, complicated new roles, doubts about forming a happy family, urgent economic needs, and modest family support. Psychological preparation has a significant influence on the condition of family harmony, so it must be well prepared. Preparedness is needed for the bride and groom to adapt to anticipate complicated family problems. The bride and groom endeavored to obtain comprehensive education related to physical, psychological, social, and cultural changes to adapt constructively in their marriage. Keywords: Bride and Groom, Marriage, Psychological Preparation